Pengaruh Penyediaan Infrastruktur Daerah Terhadap Pertumbuhan Ekonomi di Kabupaten Gunung Mas - Alie, Asri (Economie: Jurnal Ilmu Ekonomi, 2023)
This study aims to analyze the influence of regional infrastructure, road infrastructure, electricity, education and health on economic growth in Gunung Mas District. The research method is quantitative by using secondary time series data from 2000-2017. Data were analyzed using multiple linear analysis. The results of the study show that partially the variables of road, electricity and education infrastructure have a positive and significant effect on economic growth, except health infrastructure that does not affect economic growth. Simultaneously the independent variables have a positive and significant effect on economic growth. The value of R square is 0.743, which means that 74.3 percent of infrastructure variables are able to explain economic growth in Gunung Mas Regency.